Digital Poverty and Connectivity Disparities in South Sumatra: Mapping and Policy Implications - Yurista, Rika; Budiyanto, M. Nur; Abduh, Muhammad (Journal Public Policy, 2024)
Digital poverty, defined as the inability to access and utilize information and communication technology (ICT), remains a critical issue in South Sumatra Province. This study aims to map digital poverty and connectivity disparities across districts and cities, analyze their distribution, and assess their relationship with macro poverty. Using Barrantes’ (2007) framework, this research employs descriptive statistical analysis based on the National Socio-Economic Survey (Susenas) data from March 2023. The study utilizes the digital poverty index and macro index to classify regions into quadrants. The findings reveal that the highest levels of digital poverty are observed in Empat Lawang Regency (52.75%), North Musi Rawas Regency (44.625%), and PALI Regency (44.51%). Conversely, Prabumulih City (80.27%), Palembang City (80.17%), and Ogan Komering Ulu (74.43%) exhibit the highest levels of digital connectivity. These disparities highlight the urgent need for targeted policy interventions. Recommended strategies include digital literacy enhancement, improved internet access, and strengthened digital infrastructure, particularly in high-poverty regions. Effective implementation of these initiatives is crucial to reducing digital poverty and supporting sustainable economic development in South Sumatra Province.